2019
DOI: 10.1007/s13213-019-01537-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tobacco–peanut relay intercropping on soil bacteria community structure

Abstract: Purpose A reasonable cultivation pattern is beneficial to maintain soil microbial activity and optimize the structure of the soil microbial community. To determine the effect of tobacco−peanut (Nicotiana tabacum−Arachis hypogaea) relay intercropping on the microbial community structure in soil, we compared the effects of relay intercropping and continuous cropping on the soil bacteria community structure. Methods We collected soil samples from three different cropping patterns and analyzed microbial community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Another study also reported on changes in the soil bacterial community associated with plant growth and development in response to crop rotation (Panke-Buisse et al, 2015). We also found that the OTU number and Shannon diversity index was much higher for rhizospheric communities of C. yanhusuo than of other medicinal plants, or even peanut (Gao et al, 2019;Wang X.L. et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…Another study also reported on changes in the soil bacterial community associated with plant growth and development in response to crop rotation (Panke-Buisse et al, 2015). We also found that the OTU number and Shannon diversity index was much higher for rhizospheric communities of C. yanhusuo than of other medicinal plants, or even peanut (Gao et al, 2019;Wang X.L. et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…Thus, attempts have been to assess the impact of IC on rhizosphere microbiota. Total microbial communities ( Taschen et al, 2017 ; Li et al, 2018 ; Gao et al, 2019 ; Liu et al, 2021 ; Tang et al, 2021 ) and specific functional guilds (e.g., ammonia oxidizing bacteria, Song et al, 2007 ; diazotrophic Proteobacteria, Solanki et al, 2020 ) from the total root systems of plant genotypes associated in IC have been analyzed. These reports evidenced that rhizosphere microbiota from IC and sole-cropping (SC) differ significantly, these differences being more strongly expressed for bacteria than for fungi ( Gong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pearson’s correlation analysis revealed that the WT and GM sugarcane bacterial communities had different relationships with the environmental factors ( Figure 2B ), which further demonstrated that the two sugarcane varieties may shape different rhizosphere bacterial structures due to their influences on soil environmental factors ( Zhang et al, 2016 ). Direct contact between the roots of two intercropped plants leads to interactions between their root exudates, which in turn affects the bacterial community structure ( Gao et al, 2019 ; Yu et al, 2019 ). Therefore, we speculated that root exudation may play a positive role in maintaining or modifying the community structure of rhizosphere soil microbes, the enrichment of which may considerably impact plant growth ( Huangfu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%